(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Tea waste, an abundant agro-industrial byproduct, has garnered attention as a potential organic soil amendment due to its rich bioactive compounds and nutrient content. The rising global demand for sustainable agricultural practices has intensified interest in the valorization of agro-industrial waste. This study investigates the potential of post-consumer tea-spent residues—Green Tea (GT), Tea Granules (TG), and Tea Dust (TD), along with their sugar and milk-based variants (GTS, TGS, TDS, TGMS, TDMS) as nutrient-rich soil amendments and plant growth enhancers. Comprehensive proximate and mineral analyses were conducted, followed by soil quality assessment and plant growth trials using Trigonella foenum-graecum (fenugreek). Soil treated with GT and TG variants exhibited improved physicochemical properties, including increased moisture retention, higher water-holding capacity, and enhanced porosity. Plant growth assessments revealed significantly enhanced germination rates, chlorophyll-a content, and carotenoids in GT and TG-amended soils, compared to controls and raw TD treatments. These findings underscore the dual benefits of tea-spent residues as nutrient sources and plant growth promoters. The study highlights a sustainable pathway for agro-waste valorization, supporting circular bioeconomy models and eco-friendly farming. Further research is recommended to optimise application rates and investigate long-term effects on plant health and soil microbiota.